Does culture make a difference ? : Progress and development in India and its implications for international cooperation : Conference Papers (Calcutta, 2008)
This volume contains the most important contributions to the conference and several articles that have been written exclusively for this publication. Tracing the contours of many views around the ideas of progress, modernization and development, coming at them from the perspective of diverse disciplinary specialisms and activisms, this collection helps us comprehend in practical terms various oft-used words such as 'progress', 'development', 'dynamics', 'change' or 'modernization.
Keywords: Social change